Perioperative antibiotic prophylaxis in open tracheostomy: A preliminary randomized controlled trial - Pichit Sittitrai (2018)
© 2018 IJS Publishing Group Ltd Background: The efficacy of perioperative antibiotic prophylaxis for prevention of wound infection in open tracheostomy has been minimally studied and remains controversial. Methods: A preliminary double-blind, randomized, placebo-controlled trial was conducted. A total of 159 patients who underwent open tracheostomy were enrolled, and 88 patients were excluded because of lack of desire to participate in research, emergency condition, administration of other antibiotics, immunocompromise, or cervical skin infection. The remainings were randomly assigned to an antibiotic group or a control group. Another 11 patients were excluded after the randomization due to intraoperative contamination, death from the underlying disease, receiving other antibiotics, or lost to the follow-up. A total of 30 patients in each group were qualified for analysis. In the antibiotic group, clindamycin was intravenously administered 30 min before the incision and every 8 h after the operation for 24 h. In the control group, an equal volume of sterile saline was administered. Results: Wound infection developed in 2 patients (6.7%) in the antibiotic group and 7 patients (23.3%) in the control group (p = 0.08). In multivariate analysis, smoking and previous neck irradiation were the significant risk factors for wound infection (p = 0.042 and 0.019, respectively). The mean length of hospital stay after tracheostomy in patients with and without wound infection were 17 ± 2 days and 4 ± 2 days, respectively (p = 0.013). Conclusion: The result of this preliminary study reveals that antibiotic prophylaxis reduced tracheostomy wound infection rate from 23.3% to 6.7% although it was not statistically significant. However, wound infection may lead to serious complications and prolonged postoperative length of hospital stay, and therefore proper perioperative antibiotics should be considered in patients who are not receiving other antibiotics, and particularly in patients with risk factors for wound infection.